Estimating the Increase in the Mechanical Characteristics of Self-Compacting Lightweight Concrete Incorporating Pumice and Steel Fibers - Masoud Dadkhah; Reza Rahgozar; Ehsan Barahouei Pasandi; Peyman Rahgozar (Journal of Rehabilitation in Civil Engineering)
The incorporation of lightweight concrete significantly reduces the weight of structures. However, achieving proper density and ensuring the ease of concrete placement in structures with dense reinforcement has driven the development of self-compacting lightweight concrete (SCLC). Despite its advantages, SCLC exhibits brittleness similar to that of normal concrete. To address this limitation, steel fibers (SFs) can be integrated into SCLC to enhance its properties. In this study, SCLC was first produced using pumice aggregate. Fresh concrete properties were evaluated through Slump Flow, T50, V-Funnel, and L-Box tests, leading to the selection of an optimal mix design. Subsequently, SFs were added to the SCLC at proportions of 0.125%, 0.25%, and 0.5% by volume. The effects of SFs on the mechanical properties of SCLC were assessed through hardened concrete tests, including compressive strength, splitting tensile strength, and flexural strength tests. The results demonstrated that adding SFs to SCLC containing pumice aggregate improves mechanical strength, with the enhancement continuing up to 0.5% fiber content by volume. A predictive method for estimating the strength development of hardened samples at varying SF percentages was proposed. According to the findings, the addition of 0.25%, 0.125%, and 0.25% SFs achieved the most significant enhancements in compressive, tensile, and flexural strengths, respectively. Furthermore, incorporating pumice and SFs in concrete contributes to reduced environmental impact, improved durability, and cost reduction, promoting sustainable and efficient construction practices. Finally, three equations were developed to estimate the 28-day compressive, tensile, and flexural strengths based on SF content. Additionally, two equations were provided to predict tensile strength and modulus of rupture from the 28-day compressive strength.